2015
DOI: 10.1111/mmi.13281
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic‐di‐AMPsynthesis by the diadenylate cyclaseCdaAis modulated by the peptidoglycan biosynthesis enzymeGlmMinLactococcus lactis

Abstract: SummaryThe second messenger cyclic-di-adenosine monophosphate (c-di-AMP) plays important roles in growth, virulence, cell wall homeostasis, potassium transport and affects resistance to antibiotics, heat and osmotic stress. Most Firmicutes contain only one c-di-AMP synthesizing diadenylate cyclase (CdaA); however, little is known about signals and effectors controlling CdaA activity and c-di-AMP levels. In this study, a genetic screen was employed to identify components which affect the c-di-AMP level in Lacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(134 citation statements)
references
References 57 publications
4
125
1
4
Order By: Relevance
“…Downregulation of GlmS contributes indirectly to reducing the pool of UNAG synthesis, and a small UNAG pool increases levels of the essential cyclic 3,5-diadenosine monophosphate (c-di-AMP) second messenger (Witte et al, 2008; Zhu et al, 2016). Changes in the intracellular level of c-di-AMP, which play an essential role in K + transport and cell wall homeostasis (Gundlach et al, 2017), indirectly increase the intracellular (p)ppGpp pool (Rao et al, 2010; Corrigan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Downregulation of GlmS contributes indirectly to reducing the pool of UNAG synthesis, and a small UNAG pool increases levels of the essential cyclic 3,5-diadenosine monophosphate (c-di-AMP) second messenger (Witte et al, 2008; Zhu et al, 2016). Changes in the intracellular level of c-di-AMP, which play an essential role in K + transport and cell wall homeostasis (Gundlach et al, 2017), indirectly increase the intracellular (p)ppGpp pool (Rao et al, 2010; Corrigan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these results suggested that CdaA is the major diadenylate cyclase in B. subtilis and that c-di-AMP produced by this enzyme is the cause of c-di-AMP toxicity. Zhu et al have isolated suppressor mutants that overcome the salt sensitivity of Lactococcus lactis strains lacking the single c-di-AMPdegrading phosphodiesterase (28). With an impressive set of more than 60 distinct mutations affecting CdaA, and thus reduced levels of c-di-AMP, this study convincingly reinforced the conclusion that c-di-AMP accumulation causes osmosensitivity in L. lactis (28).…”
Section: Mutations Affecting the Major Diadenylate Cyclase Cdaa Prevementioning
confidence: 60%
“…The suppressor mutants that are more resistant to heat stress carry mutations, and two distinct mutations affecting the single diadenylate cyclase CdaA are involved in this resistance: a V76G substitution at the outer side of the third transmembrane helix, and a frameshift at the C terminus-encoding end of the cdaA gene that results in the addition of a 32-amino-acid tail. Interestingly, a mutation corresponding to the V76G mutation was also found in the L. lactis suppressor screen, and mutations affecting the C terminus of the protein were detected in both B. subtilis and L. lactis (9,28). Both mutations resulted in a severe reduction of the c-di-AMP concentrations and restored the wild-type levels of the nucleotide.…”
Section: Mutations Affecting the Major Diadenylate Cyclase Cdaa Prevementioning
confidence: 92%
See 2 more Smart Citations